Possibilities of Metaverse: The Second Life - Alden Fernandes; Prof. Sunetra Chatterjee (International Journal of Engineering and Management Research, 2022)
Metaverse because the latest nonsensicality has attracted nice attention from each business and domain. Metaverse seamlessly integrates the important world with the virtual world and permits avatars to hold out wealthy activities together with creation, display, diversion, social networking, and mercantilism. Thus, it is promising to make an associate degree exciting digital world and to rework a more robust physical world through the exploration of the metaverse. during this survey, we tend to dive into the metaverse by discussing how Blockchain and AI (AI) fuse with it through investigation of the progressive studies across the metaverse elements, digital currencies, AI applications within the virtual world, and blockchain-empowered technologies. more exploitation and knowledge base analysis on the fusion of AI and Blockchain towards metaverse will certainly need collaboration from each domain and industry. we tend to would like our survey will facilitate researchers, engineers, and associate degreed educators to build an open, fair, and rational future metaverse.